27.0k views
2 votes
-3(12 - m) = -1(m - 8)

User VenoMKO
by
6.1k points

2 Answers

5 votes

Final answer:

To solve the equation -3(12 - m) = -1(m - 8), distribute the -3 and -1 to the terms in parentheses, simplify both sides, combine like terms, and solve for m. The solution is m = 11.

Step-by-step explanation:

To solve the equation -3(12 - m) = -1(m - 8), we can start by distributing the -3 and -1 to the terms in parentheses:



-3 * 12 + 3 * m = -1 * m + 1 * 8



Next, simplify both sides of the equation:



-36 + 3m = -m + 8



Combine like terms on each side:



3m + m = 8 + 36



4m = 44



Divide both sides of the equation by 4:



m = 11

User Dave Martin
by
4.6k points
5 votes

Answer:

m = 7

Step-by-step explanation:

- 3(12 - m) = - 1(m - 8)

- 36 - (- 3m) = - m - 8

- 36 + 3m = - m - 8

- 36 + 3m + m = - m + m - 8

- 36 + 4m = - 8

- 36 + 36 + 4m = - 8 + 36

4m = 28

4m ÷ 4 = 28 ÷ 4

m = 7

User Felk
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.